Technical aspects of endobronchial ultrasound-guided transbronchial needle aspiration: CHEST guideline and expert panel report - Wahidi, Momen M.; Herth, Felix; Yasufuku, Kazuhiro; Shepherd, Ray Wesley; Yarmus, Lonny; Chawla, Mohit; Lamb, Carla; Casey, Kenneth R.; Patel, Sheena; Silvestri, Gerard A.; Feller-Kopman, David J. (Chest, 2016)
Background - Endobronchial ultrasound (EBUS) was introduced in the last decade, enabling real-time guidance of transbronchial needle aspiration (TBNA) of mediastinal and hilar structures and parabronchial lung masses. The many publications produced about EBUS-TBNA have led to a better understanding of the performance characteristics of this procedure. The goal of this document was to examine the current literature on the technical aspects of EBUS-TBNA as they relate to patient, technology, and proceduralist factors to provide evidence-based and expert guidance to clinicians. - Methods - Rigorous methodology has been applied to provide a trustworthy evidence-based guideline and expert panel report. A group of approved panelists developed key clinical questions by using the PICO (population, intervention, comparator, and outcome) format that addressed specific topics on the technical aspects of EBUS-TBNA. MEDLINE (via PubMed) and the Cochrane Library were systematically searched for relevant literature, which was supplemented by manual searches. References were screened for inclusion, and well-recognized document evaluation tools were used to assess the quality of included studies, to extract meaningful data, and to grade the level of evidence to support each recommendation or suggestion. - Results - Our systematic review and critical analysis of the literature on 15 PICO questions related to the technical aspects of EBUS-TBNA resulted in 12 statements: 7 evidence-based graded recommendations and 5 ungraded consensus-based statements. Three questions did not have sufficient evidence to generate a statement. - Conclusions - Evidence on the technical aspects of EBUS-TBNA varies in strength but is satisfactory in certain areas to guide clinicians on the best conditions to perform EBUS-guided tissue sampling. Additional research is needed to enhance our knowledge regarding the optimal performance of this effective procedure.